« Le sens des jardins » : une question embarrassante - Catherine Chomarat-Ruiz (Projets de Paysage)
If a garden is considered as a set of signs to be deciphered, it refers to the intention which preceded its elaboration, to the direction its evolution takes, and to its signification as such. From then on, it raises the issue of its interpretive framework or, even better, of the most efficient interpretation system to report on these three possible conceptions of the meaning. From this assessment and its analysis, this article pleads for an attention given to the meaning of the gardens contrary to a mere positivist conception of history à or a simple sensitive approach. Then, it compares an hermeneutical entry, then a deconstructivist conception of history. It finally draws its conclusion on the necessity to initiate an epistemology of the history of gardens.